2011
DOI: 10.1371/journal.pone.0025557
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the Lipopolysaccharide to Resistance of Shigella flexneri 2a to Extreme Acidity

Abstract: Shigella flexneri is endemic in most underdeveloped countries, causing diarrheal disease and dysentery among young children. In order to reach its target site, the colon, Shigella must overcome the acid environment of the stomach. Shigella is able to persist in this stressful environment and, because of this ability it can initiate infection following the ingestion of very small inocula. Thus, acid resistance is considered an important virulence trait of this bacterium. It has been reported that moderate acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 63 publications
2
21
0
Order By: Relevance
“…Genetically modified Y. pestis harboring fully potent LPS is completely avirulent, suggesting that the evasion of LPS-TLR4-mediated inflammation is critical for Y. pestis virulence (52,53). Very recently, two reports have highlighted in S. flexneri serotype two adaptation mechanisms involving LPS modifications and amount, respectively (54,55). LPSs contribute to the capacity of Shigella to resist acid conditions, like those encountered in the stomach, with modifications in the lipid A region, which is added with a phosphoethanolamine residue to decrease the negative charge at the bacterial surface (54).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetically modified Y. pestis harboring fully potent LPS is completely avirulent, suggesting that the evasion of LPS-TLR4-mediated inflammation is critical for Y. pestis virulence (52,53). Very recently, two reports have highlighted in S. flexneri serotype two adaptation mechanisms involving LPS modifications and amount, respectively (54,55). LPSs contribute to the capacity of Shigella to resist acid conditions, like those encountered in the stomach, with modifications in the lipid A region, which is added with a phosphoethanolamine residue to decrease the negative charge at the bacterial surface (54).…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, two reports have highlighted in S. flexneri serotype two adaptation mechanisms involving LPS modifications and amount, respectively (54,55). LPSs contribute to the capacity of Shigella to resist acid conditions, like those encountered in the stomach, with modifications in the lipid A region, which is added with a phosphoethanolamine residue to decrease the negative charge at the bacterial surface (54). Furthermore, LPS layer from Shigella grown at 30°C appeared thicker than that of cells grown at 37°C.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has shown that modification of lipid A is a strategy employed not only in A. baumannii strains but in many other Gram-negative bacteria. Recent reports have shown Shigella flexneri lipid A to be modified by pEtN groups and involved in resistance to extreme acidity (32). Loss of pEtN addition in lptA null strains (lptA encodes the pEtN transferase for the 4= position of lipid A) of Neisseria gonorrhoeae modulates resistance to complement killing and polymyxin resistance (33).…”
Section: Discussionmentioning
confidence: 99%
“…Although glucosylation does not appear to change this role in Salmonella and Shigella (43,45,46), other cellular properties are certainly impacted in a species-specific manner. In Shigella, glucosylation leads to greater invasion, which is correlated to enhanced function and exposure of the type 3 secretion system (43), and elevated acid tolerance (47). In Salmonella, glucosylation is associated with virulent isolates (48) but is not a stable property leading to antigenic (form) variation in the O serotype (45,46,49).…”
Section: Discussionmentioning
confidence: 99%